Quantum Mechanistic Studies of the Oxidation of Ethylene by Rhenium Oxo Complexes - Emmanuel Adu Fosu; Collins Obuah; Louis Hamenu; Albert Aniagyei; Michael Kojo Ainooson; Krishna K. Govender (Journal of Chemistry)
Transition-metal-mediated oxygen transfer reactions are of importance in both industry and academia; thus, a series of rhenium oxo complexes of the type ReO3L (L = O−, Cl−, F−, OH−, Br−, I−) and their effects as oxidation catalysts on ethylene have been studied. The activation and reaction energies for the addition pathways involving multiple spin states (singlet and triplet) have been computed. In all cases, structures on the singlet potential energy surfaces showed higher stability compared to their counterparts on the triplet potential energy surfaces (PESs). Frontier Molecular Orbital calculations show electrons flow from the HOMO of ethylene to the LUMO of rhenium for all complexes studied except ReO4− where the reverse case occurs. In the reaction between ReO3L (L = O−, Cl−, F−, OH−, Br−, and I−) and ethylene, the concerted [3 + 2] addition pathway on the singlet PES leading to the formation of dioxylate intermediate is favored over the [2 + 2] addition pathway leading to the formation of a metallaoxetane intermediate and subsequent rearrangement to the dioxylate. The activation and the reaction energies for the formation of the dioxylate on the singlet PES for the ligands studied followed the order O− > OH− > I− > F− > Br− > Cl− and O− > OH− > F− > I− > Br− > Cl−, respectively. Furthermore, the activation and the reaction energies for the formation of the metallaoxetane intermediate increase in the order O− > OH− > I− > Br− > Cl− > F− and O− > Br− > I− > Cl− > OH− > F−, respectively. The subsequent rearrangement of the metallaoxetane intermediate to the dioxylate is only feasible in the case of ReO4−. Of all the complexes studied, the best dioxylating catalyst is ReO3Cl (singlet surface) and the best epoxidation catalyst is ReO3F (singlet surface).